EFFECT OF THE FEED LINE ON THE RADIATION PATTERN OF THE SMALL UWB PLANAR MONOPOLE ANTENNA - Akkaya, Eren; Gunes, Filiz (YILDIZ TECHNICAL UNIV, 2012)
In this article, the effect of the common mode currents flowing on the feed line of the UWB planar monopole antenna on the radiation pattern is analysed based on the 3D Computer Simulation Technology Microwave Studio (CST MWS). Heretofore this effect has been generally neglected in the antenna design process. In this study, a comparison is made between the antenna designs with and without effect of the feed line. It is concluded the common mode currents on the feed line destructively effects on the radiation of the UWB planar monopole antenna and therefore it cannot be neglected and should be taken into account in the design process of the UWB planar monopole antenna.
Keywords: UWB Antenna; planar antenna; monopole antenna; common mode current; feed line; Engineering